Original paper Er:YAG laser evaluation in the treatment of benign neoplasms and tumorous lesions of the oral mucosa - Błochowiak, Katarzyna; Sidorowicz, Krzysztof; Sokalski, Jerzy; Witmanowski, Henryk (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2012)
Introduction: In the treatment of benign and hyperplastic fibro-epidermal tumorous oral lesions standard surgical techniques as well as Er:YAG lasers are applied. Aim: Photographic records of chosen clinical cases were used to discuss major advantages of the laser technique. The other aim of this paper was to systematize indications to the procedure and to choose the operating mode depending on clinical condition as well as the size of pathology. Some limitations and disadvantages of the laser method were shown, too, comparing to a conventional surgical treatment. Material and methods : Clinical records of 25 patients with benign neoplasms and tumourous growths on the oral mucosa qualified for the Er:YAG laser treatment were studied. Results and Conclusions : The laser method does not make histopathologic examination of the excised tissue impossible. The best quality incision is achieved with the lowest laser power and its highest frequency. Such mode limits disadvantageous thermal load, too. The greatest stromal and epidermal changes affect the smallest tissue fragments. With the haemostasis achieved in the laser technique suturing the wound can often be avoided. No sutures means preservation of the oral vestibule depth and gingival and mucosal contour, what prevents the recurrence of lesions.